Empowered to Serve? : Higher Education International Center Directors and Their Roles on Campus Internationalization - Garcia, Hugo; McNaughtan, Jon; Li, Xinyang; Leong, Mi Chelle; Herridge, Andrew Scott (Journal of International Students, 2021)
Some institutions have sought to centralize the supports they give students by developing a center or office dedicated to international students, led by a director or manager overseeing international student support. However, these directors are also not given the resources needed to fully support international students. Our study focuses on the role and empowerment of these international center leaders. A multi-institution case study approach, guided by the empowerment framework, was utilized. The first research question asked what perceptions international center directors have of the resources and support structures provided by their institutions for the growing international student population. The second research question examined how international center directors perceive their empowerment, and which dimensions of empowerment they experience, or lack. Findings include international center directors reporting their sense of empowerment is founded in their desire to serve, sense of autonomy, and the sense of meaning they find engaging in the work.